(untitled) (Journal of Mathematical Modeling and Fractional Calculus, 2025)
Skin sores (impetigo) are a frequent and contagious skin infection in young children, caus ing blisters and ulcers. It is usually not hazardous and resolves within a week of treatment or a few weeks if no treatment is used. Treatment is commonly recommended since it can shorten the length of the condition and reduce the risk of the virus spreading to others. We developed and tested a non linear hybrid fractional order model to investigate skin sores infection and the transmission dynamics. The study examines the mathematical properties of the suggested model, such as the feasible region, equilibrium points, basic reproduction number, and existence of the system’s unique solutions using Banach fixed-point theory. It also uses the appropriate lyapunov function to examine the stability of equilibrium states. This work gives a thorough examination of several hybrid fractional operators and numerically simulates the suggested skin sores system using the Laplace-Adomian decomposition approach, demonstrating its efficacy in simulating theoretical scenarios. This research advances our knowledge of the mechanisms underlying disease transmission by taking into account fractional-order dynamics and a variety of routes, offering suggestions for better disease management and control.